Non-genetic factors affecting the reproduction performance, lamb growth and productivity indices of Djallonke sheep - Gbangboche, A.B; Adamou-Ndiaye, M.; Youssao, A.K.I.; Farnir, F.; Abiola, F.A; Leroy, P.L.; Detilleux, J. (Elsevier, 2006)
Two important components that determine sheep production efficiency are reproduction and live body weight. An understanding of environmental factors affecting these traits is needed to implement optimal breeding and selection programs in Benin (West Africa). In this study, age at first lambing, length of the lambing interval, prolificacy, dam’s post-partum weights, lambs weight at weaning and productivity indices of West African Dwarf sheep (Djallonke sheep) were analyzed under research conditions. The non-genetic effects (season of birth, year of birth, parity of the ewes and sex of lambs) were determined. Age at first lambing (622.4±55.6days) was significantly (p